Development of Hydrogel‐Based Sprayable Wound Dressings for Second‐ and Third‐Degree Burns. Issue 6 (9th April 2021) - He, Jacqueline Jialu; McCarthy, Colleen; Camci-Unal, Gulden
Abstract : On‐site, prehospital care is vital for minimizing the severity of injuries caused by acute burns, especially those of the second and third degrees. Burn wounds typically have irregular shapes and depths and cover a large total body area. Due to the severity and complexity of burn wounds, traditional sheet‐like wound dressings are not always suitable. Alternatively, sprayable wound dressings can be used for convenient, quick, and large‐scale dressing changes. They can also prevent infection and secondary trauma depending on their reagent content. Sprayable wound dressings function as a therapeutic barrier that provides moisturization and pain relief, absorbs extrudates, protects against bacterial infections, and acts as a delivery system for small molecules and drugs. This review discusses the recent developments in sprayable hydrogel‐based wound dressings for high‐degree burns. An introduction to burn wound classifications, the ideal burn dressing designs and characteristics, and the current availability of commercial spray‐on burn dressings are presented. To achieve the optimal healing capacities using sprayable wound dressings, researchers are currently focusing on modifying the solution viscosities, propellant systems, and pump nozzle designs for spray formulations. Finally, the use of hydrogel‐based dressings to replace skin graft surgeries for tissue regeneration is discussed. Abstract : Sprayable hydrogel‐based burn dressings allow for rapid pretreatment of high‐degree burn wounds. The base hydrogel component can be used to encapsulate biomolecules such as drugs, antibiotics, and analgesics to alleviate pain, decrease swelling, and prevent the wound from getting infected. Due to the practicality and simplicity of the administration process, sprayable wound dressings are promising solutions for burn care.